An integrative review of negative emotions of older adults in later life - Adolfo, Cris S; Albougami, Abdulrhman Saad B; Roque, Mark Y; Aruta, John Jamir Benzon R *; Almazan, Joseph U (Wiley, 2022)
Background: Older adults are one of the most vulnerable populations requiring scientific, psychological, and clinical attention. Although several studies have explored psychoemotional needs in later life, one critical gap in the literature is a shortage of studies comprehensively reviewing negative emotional experiences and their antecedents associated with later life.